2019
DOI: 10.5194/acp-2019-493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long range and local air pollution: what can we learn from chemical speciation of particulate matter at paired sites?

Abstract: <p><strong>Abstract.</strong> We report here results of a detailed analysis of the urban and non-urban contributions to PM concentrations and source contributions in 5 European cities, namely: Shiedam (The Netherlands; NL), Lens (France; FR), Leipzig (Germany; DE), Zurich (Switzerland; CH) and Barcelona (Spain; ES). PM chemically speciated data from 12 European paired monitoring sites (1 traffic, 5 urban, 5 regional and 1 continental background) were analyzed by Positi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Figure 4 presents a comparison of the source contributions in each site based on mass concentration (in µg m −3 ). These results are in line with recent studies leading to anthropogenic and SOA sources heavily influencing urban air pollution in western Europe (Daellenbach et al, 2019;Pandolfi et al, 2020;Srivastava et al, 2018b;Weber et al, 2019). The most notable difference across all sites is the sharp decrease in mineral dust in Vif compared to the other two urban sites, and this is discussed further in Sect.…”
Section: Pm 10 Contributionsupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 4 presents a comparison of the source contributions in each site based on mass concentration (in µg m −3 ). These results are in line with recent studies leading to anthropogenic and SOA sources heavily influencing urban air pollution in western Europe (Daellenbach et al, 2019;Pandolfi et al, 2020;Srivastava et al, 2018b;Weber et al, 2019). The most notable difference across all sites is the sharp decrease in mineral dust in Vif compared to the other two urban sites, and this is discussed further in Sect.…”
Section: Pm 10 Contributionsupporting
confidence: 91%
“…Investigating the PM oxidative potential (OP) in light of its major emission sources in various urban environments can then provide valuable information to instigate air pollution abatement policies limiting health outcomes. However, spatially resolved PM source apportionment at a city scale remains a challenging task (Dai et al, 2020a, b;Pandolfi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfate may not appear clearly in the “diesel” profile since the variations in sulfate can be fully subsumed by the “sulfate” factor. However, the relationship with the primary emissions can be observed in the g-space plots ( Kim and Hopke, 2008 : Pandolfi et al, 2020 ) and adds to the total impact of the primary source.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the robustness of our PMF model, a multisite solution was used by aggregating the BCN and MSY data into a single dataset for each PM size. Previous research has shown the feasibility of applying a multisite PMF to PM 10 and PM 2.5 in the same study area (in 't Veld et al, 2021;Pandolfi et al, 2020). Applying the multisite solution did not, however, result in an adequate solution.…”
Section: Source Apportionmentmentioning
confidence: 73%
“…A considerable amount of previous research has been performed in the study area regarding sources of PM 10 , PM 2.5 , and PM 1 (Amato et al, 2009b(Amato et al, , 2016Brines et al, 2019;in 't Veld et al, 2021;Minguillón et al, 2011;Moreno et al, 2011;Pandolfi et al, 2016Pandolfi et al, , 2020Pérez et al, 2016;Querol et al, 2007;Reche et al, 2012;Viana et al, 2013). This extensive research, which has applied PMF for all PM sizes, has separately identified the same sources for all PM sizes.…”
Section: Source Apportionmentmentioning
confidence: 99%